Moisture transport by tropical plumes over the Middle East: a 30‐year climatology. (27th December 2017) - Tubi, Amit; Dayan, Uri; Lensky, Itamar M.
Abstract : This study conducts a 30‐year climatological analysis of tropical plumes (TPs) observed over the Middle East (ME). These moisture bursts, conveying water vapour from tropical Africa to the arid ME at mid‐ to upper tropospheric levels, were identified and analysed using multiple data sources and empirical tools, including satellite images, reanalysis data, backward trajectories, and calculation of moisture profiles, water vapour transport and moisture flux convergence. The analysis of the 140 days in which TPs were identified focused on three main elements: (i) TP seasonal distribution and contribution to rainfall regime, (ii) TP moisture pathways, and (iii) the mechanisms leading to TP‐induced precipitation. TPs over the ME are found to be most frequent in the winter season, with the second highest frequency observed during the spring. The estimation of TPs' contribution to the rainfall regime over the ME, the first of its kind, shows that such contribution is limited. However, extreme events may have a significant effect on the overall annual precipitation amount. Two moisture pathways are identified, exhibiting very limited mixing, if any, with the dry air mass at shallow tropospheric levels. The first, originating in tropical West Africa, is associated with the penetration of an intensified subtropical jet stream towards lower latitudes. The second, emanating from East to Central African sources, is closely associated with an anomalous anticyclonic flow over southern Arabia. Moisture conveyed by the latter pathway is supplied from sources that are closer to the target area, transported at lower atmospheric levels, and exhibits more pronounced vertical dispersion. Compared to TPs that did not lead to precipitation, precipitative TPs feature enhanced moisture transport and stronger convergence of moisture flux. Similarly, the belt of moisture flux convergence stretching from the Tropics to the ME is interrupted when non‐precipitative TPs occur but uninterrupted during precipitative events. Abstract : A 30‐year climatological analysis of tropical plumes observed over the Middle East is conducted. Two moisture pathways are identified: one originating in West Africa, associated with the southwards penetration of an intensified subtropical jet stream, and another emanating from East to Central African sources, associated with an anomalous anticyclonic flow over southern Arabia. Precipitation characteristics are also analysed. Compared to non‐precipitative tropical plumes, precipitative events feature enhanced moisture transport and stronger convergence of moisture flux.